Oral cancer burden in Sri Lanka- 2005 to 2019: does it differ with site and sex? - Upuli Perera; Achini Jayathilake; Mekala Fernando; Thanuja Wickramathunga (College of Community Physicians of Sri Lanka, 2022)
Abstract Background: Oral cancer is the commonest cancer among Sri Lankan males for decades. Objectives: To analyze the incidence trends and patterns of oral cancer in Sri Lanka between 2005 and 2019. Methods: Data on oral cancers were obtained from National Cancer Registry Sri Lanka from 2005 to 2019. Trend analysis was performed with join point software, on the age-standardized oral cancer incidence rates to examine the trends in relation to sex, age group category and the anatomical sites over a 15-year period. Results: Data of a total of 31919 oral cancer patients (males = 24982, 78.3%; females = 6937, 21.7%) were analyzed. The age‐standardized incidence rate (ASR) has increased over 15-year period in both sexes. The proportional increase in incidence was higher for males [1.9-fold increase with ASR: 9.8 to 18.9, AAPC of 5.38 (95% CI: 4.1-6.7)] than females [1.55-fold increase with ASR: 2.9 to 4.5, AAPC of 3.1 (95% CI: 1.8-4.5)] (p